Hyperuricemia and the risk of stroke incidence and mortality: A systematic review and meta-analysis - Haiyan Jiang,; Yunyi Su,; Ruixue Liu,; Xinyi Xu,; Qi Xu,; Jie Yang,; Yapeng Lin, (Archives of Rheumatology, 2025)
Objectives: The relationship between hyperuricemia (HUA) and stroke remains controversial. In this systematic review, we discuss the association between HUA and stroke. Materials and methods: The PubMed, Embase, Web of Science, and Cochrane Library were searched from their earliest records to March 13th, 2024, and additional papers were identified through a manual search. Prospective studies that provided a multivariate-adjusted estimate of the association between HUA and risk of stroke incidence and mortality, represented as relative risks (RRs) with 95% confidence intervals (CIs), were eligible. Results: A total of 22 studies including 770,532 adults were eligible and included. Hyperuricemia was associated with a significantly increasing risk of both stroke incidence (pooled RR, 1.42; 95% CI, 1.31-1.53) and stroke mortality (pooled RR, 1.53; 95% CI, 1.18-1.99) in our meta-analyses. Relative risk of stroke incidence was as follows: females (pooled RR, 1.67; 95% CI, 1.44-1.92) and males (pooled RR, 1.13; 95% CI, 1.02-1.25). Relative risk of mortality was as follows: female (pooled RR, 1.41; 95% CI, 1.31-1.52) and males (pooled RR, 1.27; 95% CI, 1.20-1.34). For the risk of stroke mortality, the association between HUA and ischemic stroke (pooled RR, 1.39; 95% CI, 1.31-1.47) was more significant than that of hemorrhagic stroke (pooled RR, 1.13; 95% CI, 1.02-1.26). Conclusion: Our study confirms an association between HUA and risk of stroke, which is more pronounced in females.